2008
DOI: 10.17221/1610-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the authenticity of fruit spirits by gas chromatography and stable isotope ratio analyses

Abstract: Winterová R., Mikulíková R., Mazáč J., Havelec P. (2008): Assessment of the authenticity of fruit spirits by gas chromatography and stable isotope ratio analyses. Czech J. Food Sci., 26: 368-375.The gas chromatographic (GC) determination of volatile constituents and the determination of 13 C/ 12 C isotope ratios by isotope ratio mass spectrometry -IRMS analysis as well as SNIF-NMR analysis of (D/H)I and (D/H)II ratios in ethanol are prospective analytical methods which can be used for checking the authenticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 10 publications
11
32
1
1
Order By: Relevance
“…The mean values of the concentration of ethyl acetate for tested samples ranged from 5.2 mg/100 mL a.a. for grape brandy produced from grape juice (type 1) to 454 mg/100 mL a.a. for plum brandy ( Table 4). The results obtained for the content of ethyl acetate in plum brandy were in correlation with those of Winterova et al, where the content of ethyl acetate in the samples of plum brandy ranged from 56.3 mg/100 mL a.a to 236/100 mL a.a [13]. Comparing these results, it can be concluded that the concentrations of ethyl acetate found in these samples are commonly acceptable.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The mean values of the concentration of ethyl acetate for tested samples ranged from 5.2 mg/100 mL a.a. for grape brandy produced from grape juice (type 1) to 454 mg/100 mL a.a. for plum brandy ( Table 4). The results obtained for the content of ethyl acetate in plum brandy were in correlation with those of Winterova et al, where the content of ethyl acetate in the samples of plum brandy ranged from 56.3 mg/100 mL a.a to 236/100 mL a.a [13]. Comparing these results, it can be concluded that the concentrations of ethyl acetate found in these samples are commonly acceptable.…”
Section: Resultssupporting
confidence: 87%
“…The content of n-butyl alcohol was also found to be low in all tested samples, ranged from 1 mg/100 mL a.a. for grape brandy produced from wine distillate to 12 mg/100 mL a.a for plum brandy. According to the investigations of Winterove et al, the higher alcohols most frequently found in low concentrations in fruit spirits were n-butyl alcohol and isobutyl alcohol [13]. They found the lowest values measured for n-butyl alcohol in sweet cherry and sour cherry brandies (0.5-3.1 mg 100mL a.a.).…”
Section: Resultsmentioning
confidence: 97%
“…Benzyl alcohol and 2-phenylethanol have been identified and described as contributors to the flavor of elderberry (Mikova et al 1984). Terpenes are another chemical compound group, which have influence on sensory properties of fruit spirit beverages and liqueurs (Christoph and Bauer-Christoph 2006;Winterová et al 2008). In this study, 18 terpenes were identified; most of them may affect the pleasant fruity and herbaceous flavor of the BOnisiówka^.…”
Section: Gc×gc-tofms Analysismentioning
confidence: 72%
“…The section lasiophyton is characterized by the fact that the vines twine to the right, that is, in a clockwise direction when viewed from the ground upwards, whereas species in section Enantiophylum twine to the left (Onwueme and Winston, 1994). The PCA analysis is a way of identifying patterns in the data and expressing the data in such a way as to highlight their similarities and differences (Winterota et al, 2008). Traits such as the tendency of the tuber to branch, tuber shape, leaf density, number of tubers per seedbed, flowering, spines on stem base, spines on stem above base, spines length and plant vigor were positive for PC1 and PC2, thus contributing to the maximum diversity of D. dumetorum accessions, whereas in Ekona, we had traits such as spines on stem base, spines on stem above base, spines length and tuber length, roots on tuber surface and place of roots on the tuber surface.…”
Section: Qualitative Charactermentioning
confidence: 99%